Pelatihan keterampilan konseling skills training for counselling /Franscesco Inskipp; Penerjemah, Hellly Prajitno Soetjipto, Sri Mulyantini Soetjipto - Inskipp, Francesca; Helly Prajitno Soetjipto (Pustaka Pelajar, 2012)
xv,188 hlm.; 23cm